Genome-wide association study of milk fatty acid composition in Italian Simmental and Italian Holstein cows using single nucleotide polymorphism arrays - Palombo, V; Milanesi, M. [UNESP]; Sgorlon, S.; Capomaccio, S.; Mele, M.; Nicolazzi, E.; Ajmone-Marsan, P.; Pilla, F.; Stefanon, B.; D'Andrea, M. (Elsevier B.V., 2018)
Bovine milk is important for human nutrition, but its fat content is often criticized as a risk factor in cardiovascular disease. Selective breeding programs could be used to alter the fatty acid (FA) composition of bovine milk to improve the healthiness of dairy products for human consumption. Here, we performed a genome-wide association study (GWAS) on bovine milk to identify genomic regions or specific genes associated with FA profile and to investigate genetic differences between the Italian Sirnmental (IS) and Italian Holstein (IH) breeds. To achieve this, we first characterized milk samples from 416 IS cows and 436 III cows for their fat profile by gas chromatography. Subjects were genotyped with single nucleotide polymorphism array and a single-marker regression model for GWAS was performed. Our findings confirm previously reported quantitative trait loci strongly associated with bovine milk fat composition. More specifically, our GWAS results revealed significant signals on chromosomes Dos taurus autosome 19 and 26 for milk FA. Further analysis using a gene-centric approach and pathway meta-analysis identified not only some well-known genes underlying quantitative trait loci for milk FA components, such as FASN, SCD, and DGAT1, but also other significant candidate genes, including some with functional roles in pathways related to Lipid metabolism. Highlighted genes related to FA profile include ECI2, PCYT2, DCXR, G6PC3, PYCR1, and ALG12 in IS, and CYP17A1, ACO2, PL4K2A, GOT1, GPT, NT5C2 PDE6G, POLR3H, and COX15 in IH. Overall, the breed-specific association outcomes reflect differences in the genetic backgrounds of the IS arid III breeds and their selective breeding histories.
Keywords: milk lipid content; genome-wide association study; cow